Socio-semiotic Analysis of a Bauhaus Chessboard - Barbetti, Enrico (E|C, 2024)
This article explores the intricate relationship between the Bauhaus and the social values in which it is placed. Operating as a public school in Weimar Republic Germany, the Bauhaus faced the challenge of navigating the escalating rhetoric of conflict at the time. We aim to illustrate how the Bauhaus strategically positioned itself in a belligerent discursive political context through the expression of certain educational values. Focusing on Bauhaus’ strategy for aggressive discourses, the article analyses an intriguing example: Josef Hartwig’s iconic chessboard. Through configurational, taxic, and functional analyses, the article reveals the layers of meaning embedded in Hartwig’s chessboard and shows a transformative narrative. The chessboard, traditionally associated with conflict, becomes, with Hartwig, an educational device. A shift from destruction to construction, reflecting the entire Bauhaus ethos.